Altered regional loading patterns on articular cartilage following meniscectomy are not fully restored by autograft meniscal transplantation. Issue 3 (March 2015) - Wang, H.; Chen, T.; Gee, A.O.; Hutchinson, I.D.; Stoner, K.; Warren, R.F.; Rodeo, S.A.; Maher, S.A.
Summary: Objective: To quantify the changes in regional dynamic loading patterns on tibial articular cartilage during simulated walking following medial meniscectomy and meniscal transplantation. Methods: Seven fresh frozen human cadaveric knees were tested under multidirectional loads mimicking the activity of walking, while the contact stresses on the tibial plateau were synchronously recorded using an electronic sensor. Each knee was tested for three conditions: intact meniscus, medial meniscectomy, and meniscal transplantation. The loading profiles at different locations were assessed and common loading patterns were identified at different sites of the tibial plateau using an established numerical algorithm. Results: Three regional patterns were found on the tibial plateau of intact knees. Following medial meniscectomy, the area of the first pattern which was located at the posterior aspect of the medial plateau was significantly reduced, while the magnitude of peak load was significantly increased by 120%. The second pattern which was located at the central-posterior aspects of the lateral plateau shifted anteriorly and laterally without changing its magnitude. The third pattern in the cartilage-to-cartilage contact region of the medial plateau was absent following meniscectomy. Meniscal transplantation largely restored the first pattern, but it did not restore the other two patterns. Conclusion: There are site-dependent changes in regional loading patterns on both the medial and lateral tibial plateau following medial meniscectomy. Even when a meniscal autograft is used where the geometry and material properties are kept constant, the only region in which the loading pattern is restored is at posterior aspect of the medial plateau.